Supplier selected relationships: choosing friends, over family. (2nd December 2009) - Clements, Michael D.J.; Dean, David L.; Cohen, David A.
This paper establishes and tests a framework enabling suppliers to measure the worth of relationships with buyers. This non-conventional perspective invites the consideration of the supplier's perspective on how relationships are valued. Given the constraints on suppliers limiting distribution by participating in relationships geared to benefit the buyer at the supplier's expense, this study tests food manufactures in New Zealand. Literature suggests a key driver for integration is mutual benefit, therefore it is argued that by understanding which relationship values distinguish between the supplier relationship levels, both the buyer and supplier then develop appropriate relationships to enhance supply chain integration.